PEP06 polypeptide 30 is a novel cluster-dissociating agent inhibiting αv integrin/FAK/Src signaling in oral squamous cell carcinoma cells - Gulnara Tuguzbaeva; Er Yue; Xi Chen; Lina He; Xinlei Li; Jiaming Ju; Ying Qin; Valentin Pavlov; Yanjie Lu; Wenting Jia; Yunlong Bai; Yumei Niu; et al. (Elsevier, 2019)
Collectively migrating tumor cells have been recently implicated in enhanced metastasis of epithelial malignancies. In oral squamous cell carcinoma (OSCC), αv integrin is a crucial mediator of multicellular clustering and collective movement in vitro; however, its contribution to metastatic spread remains to be addressed. According to the emerging therapeutic concept, dissociation of tumor clusters into single cells could significantly suppress metastasis-seeding ability of carcinomas. This study aimed to investigate the anti-OSCC potential of novel endostatin-derived polypeptide PEP06 as a cluster-dissociating therapeutic agent in vitro. Firstly, we found marked enrichment of αv integrin in collectively invading multicellular clusters in human OSCCs. Our study revealed that metastatic progression of OSCC was associated with augmented immunostaining of αv integrin in cancerous lesions. Following PEP06 treatment, cell clustering on fibronectin, migration, multicellular aggregation, anchorage-independent survival and colony formation of OSCC were significantly inhibited. Moreover, PEP06 suppressed αv integrin/FAK/Src signaling in OSCC cells. PEP06-induced loss of active Src and E-cadherin from cell-cell contacts contributed to diminished collective migration of OSCC in vitro. Overall, these results suggest that PEP06 polypeptide 30 inhibiting αv integrin/FAK/Src signaling and disrupting E-cadherin-based intercellular junctions possesses anti-metastatic potential in OSCC by acting as a cluster-dissociating therapeutic agent. KEY WORDS: Oral squamous cell carcinoma, Tumor cell clusters, Collective migration, Metastasis, αv integrin/FAK/RC signaling, RGD